Where do I fit? Lee Maracle’s “Bobbi Lee Indian Rebel” and literature - Salles, Juliana (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2014)
Native-Canadian author Lee Maracle is a renowned writer in Canadian literature nowadays. Nevertheless, up to the 1970’s, very little had been said about Native literature, and only from then on, Native writers have gained visibility. The current article deals with Maracle’s first work Bobbi Lee Indian Rebel (1975), problematizing the differences between both of its editions (1975 and 1990), attempting to bring evidences that this work can indeed be considered literature.